Mastering Effective Sentences and Motivation on the Ability of Writing Narratives in Primary School - Sugini, Sugini; Hermawan, Tifani; Barzegar, Somayeh; Androutsos, Polyvios (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The overarching objective of this research is to investigate the correlation of mastery of effective sentences and learning motivation on the ability to write narratives among fifth-grade elementary school students. Methodology: The research is quantitative correlational. The study population consists of 168 class V students from Gugus Adiwiyata State Elementary School. Simple Random Sampling was used to select a sample of 100 students. Data collection methods include interviews, tests, document analysis, and questionnaires. Research instruments include interview guidelines, test instruments, assessment guidelines, and questionnaires. Prerequisite tests were conducted. Hypothesis testing techniques involve simple and multiple linear regression, t-tests, F-tests, and determinant coefficients. Main Findings: The study, conducted at the high school level with a population of 47 students, reveals that learning motivation significantly influences student learning outcomes. Higher learning motivation correlates with better learning achievement compared to students with low motivation. Novelty/Originality of this study: The mastery of effective sentences and learning motivation) demonstrate an influence on the ability to write narratives. Specifically, Mastery of effective sentences contributes 21.3% to students’ narrative writing ability. Learning motivation contributes 10.3% to the same ability. Together, these factors significantly impact narrative writing (Fcount > Ftable, 45.147 > 3.05), with an overall influence contribution of 38.7%. The remaining 31.3% is influenced by other factors. Based on these findings, teachers should focus on enhancing both sentence mastery and student motivation to improve narrative writing skills.